Values and well-being – how are individual values associated with subjective and eudaimonic well-being? - Bojanowska, Agnieszka; Czerw, Agnieszka (Polish Psychological Bulletin, 2020)
Schwartz created a circle of values reflecting people’s individual systems of goals and motivations. These values can be grouped into different dimensions: self-protection versus self-growth and concentration on others versus concentration on self. In the present study, we analysed how these dimensions are related to hedonic and eudaimonic well-being; N=747 participants, representative of the general Polish population, completed the Portraits Value Questionnaire, Satisfaction with Life Scale and Questionnaire for Eudaimonic Well-being (online study). A series of models were tested using structural equation modelling. We found that concern for self and self-protection values were related to higher hedonic well-being, whereas concern for others and growth values were related to its lower levels. However, growth and concern for others were positively linked to eudaimonic well-being, but they may also positively and indirectly impact hedonic well-being (suppression effect). These results suggest that some values are associated with a feeling of self-realisation at the cost of current hedonic well-being.
Keywords: values; hedonic well-being; eudaimonic well-being; individual wealth